Tingkat kelulusan hidup dan regenerasi teripang gamat lumpur, Stichopus hermanii, hasil metode transverse fission - Budikase, Arter; Salindeho, Indra R.N.; Mudeng, Joppy D. (e-Journal BUDIDAYA PERAIRAN, 2019)
The research was aimed to figure out the survival rate and the regeneration rate of  the sea cucumber, Stichopus hermanii, seeds generated from the  transverse fission method.  The research was conducted in the Talengen Gulf, the District of Sangihe Islands, at the field research station of the Nusa Utara State Polytechnic.  The tested animals, Stichopus hermanii, were collected from the waters around the Talengen Gulf.  Specimens of the sea cucumber, lengthened 9 to 15cm, were transported by boat to the site of the experiment and kept in plastic mesh-cages. Fourteen individuals then were transversely tied in the middle of the body antero-posteriorly to induce fission, hence there were 28 new individuals were generated, which were composed of 14 anterior seeds and 14 posterior seeds.  The seeds then were kept in 6 plastic mesh cages, where the anterior individuals were separated from posterior ones.  The cages were placed at the bottom of the sea waters where the sea cucumber might have access to substrate and sea grasses around the cages.   The time required by the newly fissioned cucumbers to seal off the open wound, the wound recovery time, the survival rate of the seeds and the regeneration  rate of the new integument connective tissue were among the data collected during the experiment.   The regeneration rate of the new integument connective tissue was indicated by development of a protuberance at the median of the healed wound.  The results show that the survival rate of the Stichopus hermanii seeds generated from transverse fission method were 100% for 40 days post-fission.   The average time for the newly cut cucumber to seal off the open wound is 4 minutes.  The average time for the seeds either anterior or posterior individuals, to recover the wound is aroung 25-28 days.  The protruberance of the newly regeneration integument connective tissue is appeared at day 30.  There is no significant difference between anterior and posterior seeds in regenerating the protuberance of the new integument connective tissue, after 40 days post-fission.Keywords:  asexual, reproduction, transverse fission, survival rate, regeneration